Structural form of bridges reflecting construction processes - Yusuke Mizuno; Yoshiaki Kubota (Fracture and Structural Integrity)
The structural form of a bridge during construction is strongly affects its structural form after completion, with innovative construction processes sometimes leading to innovative bridge designs. It is thus important to consider the construction process during bridge design methods. This approach could be applied not only to new construction but also to replacements, reconstructions, or reinforcements. One of the authors has previously systematized the structural forms of bridges and clarified the principles. This study aims to extend these principles to construction systems. Changes in the structural systems of the construction processes and systematization of the relationship between a completed bridge and construction process in a design are illustrated. Three types of structural systems (suspension, beam, and arch systems) were analysed in terms of material efficiency and time efficiency for corresponding construction states of construction, completed, retrofitted, and retrofitting. Each system exhibited different levels of efficiency at different levels of efficiency at different states of construction. This systematization enables the application of a variety of conventional construction methods in a system. This would be helpful in developing new construction methods and designs for bridges